How do immobilised cell-adhesive Arg–Gly–Asp-containing peptides behave at the PAA brush surface?. Issue 16 (2nd November 2018) - Guskova, Olga; Savchenko, Vladyslav; König, Ulla; Uhlmann, Petra; Sommer, Jens-Uwe
ABSTRACT: Bio-engineered surfaces that aim to induce normal cell behaviour in vitro need to 'mimic' the extracellular matrix in a way that allows cell adhesion. In this computational work, several model cell-binding peptides with a minimal cell-adhesive Arg–Gly–Asp sequence are investigated in the bulk as well as immobilised on a soft surface. For this reason, a combination of density functional theory and all-atom MD simulations is applied. The major goal of the modelling is to characterise the accessibility of the cell-recognition motif on the functionalised soft polymer surface. As a reference system, the behaviour of three peptide sequences is preliminarily studied in explicit water simulations. From the analysis of the MD trajectories, the solvent accessible surface area, the distribution of water molecules around peptide groups, the secondary structure and the thermodynamics of hydration are evaluated. Furthermore, each peptide is immobilised on the surface of a homopolymer poly(acrylic acid) brush. During MD simulations, all three peptides approach closely toward PAA brush, and their surface accessibility is characterised. Although the peptides are adsorbed onto the brush, they are not hidden by the polymer strands, with RGD unit accessible on the surface and available for guided cell adhesion.